Role of Ag+ Ions in Determining Ce3+ Optical Properties in Fluorophosphate and Sulfophosphate Glasses - Zhou, Ru; Calahoo, Courtney; Ding, Yicong; Wondraczek, Lothar (ACS Omega, 2021)
Understanding the interactions among dopant species and the role of the host lattice is of fundamental importance for the chemical formulation of optically active glasses. Here, we consider the archetypal dopant pair of Ag-Ce in complex fluorophosphate (PF) and sulfophosphate (PS) matrices, in which variable bonding environments and ligand selectivity exert distinct effects on dopant properties. The addition of Ag+ to PF glasses blue-shifts the ultraviolet (UV) cutoff wavelength of Ce3+ and enhances its photoluminescence (PL) intensity. In PS matrices, the exact opposite effect is observed: red-shifting the UV cutoff and lowering the PL intensity. No Ag-Ag pairs or cluster species were found in either matrix material; however, in PS, such clustering could be triggered by secondary broad-band UV-visible irradiation. The optical properties of Ag-Ce-codoped glasses are a result of the ionocovalent character of the Ag+-O-Ce3+ bond, the cross-relaxation process between Ag+ and Ce3+, and the redox ratio of Ce3+/Ce4+. In the PF glasses, the enhancement of the Ce3+ PL intensity is due to energy transfer from Ag+ to Ce3+ and a redox shift from Ce4+ to Ce3+. The more covalent Ag+-O-Ce3+ interactions in the PS series decrease the Ce3+/Ce4+ ratio. Moreover, photoinduced Ag clustering is facilitated in the more covalent environment, which indicates that glasses commonly used for Ag nanoparticle formation, such as silicate glasses, also possess more covalent Ag+-O bonding.
CRIS-Team Scopus Importer:2023-04-20